Bioimaging comparison between synthesized carbon quantum dots and nanodiamonds - Somayeh Marouzi; Shirin Sammak; Kayvan Sadri; Majid Darroudi (Nanomedicine Journal)
Objective(s): Scientists have been focused on finding access to the potential of different materials, incredibly natural substances. This work compared two categories of nanoscale materials based on carbon sources, including carbon quantum dots (C-QDs) and detonation nanodiamonds (DNDs). Materials and Methods: The hydrothermally synthesized C-QDs from Salvia Hispanic L. and DNDs were compared through physicochemical tests such as ultra-violet spectrophotometry (UV-Vis), Fourier transform infrared (FT-IR), X-ray diffraction (XRD), and field emission scanning microscopy (FESEM). Then, we investigated their cytotoxicity and biocompatibility on HEK293 and HepG2 cell lines, respectively. To focus on nanoparticle biodistribution and shelf life throughout the in vivo studies of rats, C-QDs and DNDs were labeled by Technetium (99mTc) radioisotope for tracking purposes. Results: The characterization and cytotoxicity outcomes of C-QDs and DNDs confirmed both cases' relative intrinsic similarity and non-toxicity, which also gained permission to enter the in vivo studies of rats.Conclusion: According to biodistribution assessments, despite the slight differences between their biological properties, C-QDs, and DNDs exhibited different bioaccumulation tendencies toward organ selection.